A Simple Indicator to Measure Welfare - Fajar, Muhammad (Euclid, 2023)
This paper proposes a welfare index derived from the welfare function by accommodating the people’s happiness index as the adjustment factor. This treatment makes the proposed welfare index different from the known welfare indicator. Other than that, the simplicity of the formula and calculation process remains the same.Keywords: welfare indicator, happiness, GDP